Micromechanical Coupled Study of Crack Growth Initiation Criterion in Pressure Vessel Steel - Rakin, M.; Sedmak, A.; Cvijovic, Z.; Zrilic, M.; Sedmak, S. (Проблемы прочности, 2004)
We present results of the combined design-theoretical investigation of the mechanism of crack growth at the onset of ductile fracture of NPP reactor pressure vessels. Micromechanical approach to the prediction of ductile fracture has been applied, according to which the volume fraction of voids in the deformed material is determined by finite-element method. On the basis of CT-specimen tests and known damage parameters, obtained on smooth spherical specimens, we obtained micromechanical criterion of crack growth initiation for ductile fracture. Представлены результаты комплексного расчетно-экспериментального исследования механизма распространения трещины на начальном этапе вязкого разрушения корпусных сталей АЭС. Использован микромеханический подход к прогнозированию вязкого разрушения, согласно которому объемное содержание пор деформируемого материала определяется методом конечных элементов. На основании проведенных испытаний образцов СТ с трещиной и имеющихся данных о параметрах разрушения гладких сферических образцов установлен микромеханический критерий начала развития трещины в условиях вязкого разрушения материала. Представлено результати комплексного розрахунково-експериментального дослідження механізму розповсюдження тріщини на початковому етапі в’язкого руйнування корпусних сталей АЕС. Використовується мікромеха- нічний підхід до прогнозування в ’язкого руйнування, згідно з яким об’ємний вміст пор деформівного матеріалу визначається методом скінченних елементів. На основі проведених випробувань зразків СТ із тріщиною та відомих даних про параметри руйнування гладких сферичних зразків установлено мікромеханічний критерій початку розвитку тріщини в умовах в ’язкого руйнування.